The Project Zlín: Everyday Life in a Materialized Utopia - Galčanová, Lucie; Vacková, Barbora (Lidé města, 2009)
This article is based on a contribution to the “Město – mýtus – identita” (City – Myth – Identity) conference. In it we attempt to consider Baťa and Zlín as a specific kind of myth which is still alive within our cultural milieu. In the text which follows we will deal with one chapter from the overall story of Zlín: with the forms of worker housing, the original assumptions around its construction and its life in everyday currency (based on in-depth interviews with the residents). With this analytical look at this unique phenomenon we wish to peer under one layer of the Zlín myth.